Do Privatisation Model, Contractual and Institutional Factors Play Any Role in Infrastructure Post-privatisation Efficiency? Exploring Port Concessions in Nigeria. (December 2013) - Adi, Bongo; Ndukwe, Ernest; Iheanachor, Nkemdilim; Dim, Chukwuma
Privatisation is often seen as the key to achieving efficiency in infrastructure service delivery. In most cases, however, the model of privatisation and the right institutional environment under which they perform best are ignored in addressing the privatisation-to-efficiency debate. Recognising this, we seek to underscore the contractual and institutional factors influencing infrastructure post-privatisation efficiency in Landlord port models as applied in Nigeria's port reform. In so doing, the study explores the Landlord port privatisation model in Nigeria. The paired t -test and Wilcoxon signed rank sum test are employed to determine if there are significant improvements in port output (general cargo throughput, liquid bulk throughput, number of vessels, gross registered tonnage and container traffic) and efficiency (average waiting time, turnaround time, berth occupancy rate) proxies between the pre-concession, transition and post-concession periods in Nigeria. The result of these tests indicates that although there are significant improvements in the port output proxies, efficiency in the port did not improve significantly. The study identified lack of appropriate legal framework, weak regulatory capacity, absence of efficiency targets in concession contract and non-adherence to investment targets as the major constraints to efficiency gain in the Landlord port model.